Affective Governmentality in Food Delivery Platforms: A Study of Bolt Food Riga Push Notifications - Spuriņa, Maija; Ķešāne, Iveta (Qualitative Sociology Review, 2025)
The paper uses a governmentality perspective to discuss the issue of control in food delivery platforms through analysis of 4083 push notifications sent by the Bolt Food platform to its couriers in Riga from 2020 to 2023. It examines intensity, rationalization, subjectification, and the use of emojis in push notifications and demonstrates affective governmentality technology to control labor mobility. The analysis contributes to the literature on algorithmic management that focuses predominantly on the control embedded in the platform application. Suppose a platform application is viewed as an algorithmic panopticon in which a worker is free to enter or exit by signing on or off. In that case, other semi-automated control technologies, such as push notifications, are affective persuasive tools for bringing workers into the panopticon that limits workers’ autonomy and control.